The Formation of Indicator Framework for Effective Assessment of Investment Attractiveness of the Region - Vershinina, Anna A.; Zhdanova, Olga A.; Maksimova, Tatiana P.; Perepelitsa, Denis G. (International Journal of Economics and Financial Issues, 2015)
Despite the in-depth study of many theoretical aspects of investment activities and assessment of investment attractiveness, today the impact of the investment policy on the development of an effective strategy and the formation of favorable investment climate is not properly reflected in the contemporary research. At the same time unstable situation in socio-economic development of Russia requires new approaches to the problem of investment activity. In this regard, the article provides indicator framework to assess properly the investment attractiveness of the region's economy relating to foreign direct investment in the current context. At that, the proposed indicator framework is based on a number of principles, which allow achieving the objective assessment of investment attractiveness of regions and feasibility of the concerned indicators. Keywords: foreign direct investment, investment activity, investment climate, assessment of investment attractiveness, region's economy. JEL Classifications: F21; F51; H77; O24